PHARMACOEPIDEMIOLOGICAL PARAMETERS OF USE OF POTENT OPIOIDS IN SAINT PETERSBURG (in the light of differences in approaches to using the drugs of this group in Russia and in the world) - M. V. Pchelintsev; E. E. Zvartau; A. N. Kubynin (Неврология, нейропсихиатрия, психосоматика)
The paper considers the pharmacoepidemiological parameters of the use of potent opioids in Saint-Petersburg in 2000-2009. These parameters are compared with those in a number of countries of the world, particularly in the Scandinavian countries that are close to Saint Petersburg in population. The reasons for the differences in the use of potent analgesics are analyzed. Approaches to prescribing the drugs of this group for non-cancer pain caused by neurological diseases in particular are also analyzed.